The Influence of the TGT Learning Model Assisted by Question Cards on IPAS Learning Outcomes - Istiqomah, Nur Hayati; Ahmadi, Farid (LPPM Undiksha, 2025)
The lack of variety in learning makes students easily bored and haveneeds help understanding the material, impacting learning outcomes. Therefore, a learning model is needed to increase students' interest and enthusiasm, such as the Team Games Tournament learning model with the help of Question Cards. The research aims to test the effect of implementing this model on students' science learning outcomes. This research is quasi-experimental in the form of a Nonequivalent Control Group Design. The subjects of this research included the entire population of fourth-grade elementary school students. The sample used was 104 students. The data collection methods used are interviews, observation, tests, and documentation. Data collection instruments with test questions, observation sheets, and interviews. The data analysis technique uses inferential statistical analysis. Data analysis uses qualitative and quantitative descriptive statistics. The results of the hypothesis test show differences in the average student learning outcomes. The results of the N-Gain test show the scores for the control class (low category) and the experimental class (medium category), meaning that there is an increase in the average of better learning outcomes in the experimental class. Based on these results, applying the Teams Games Tournament learning model assisted by Question Cards affects students' science learning outcomes.